The concept of private placement in Polish and American federal law: The comparative analysis - Balcarek, Szymon (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Private placement as an offering of securities or shares to a specific group of investors is eagerly chosen by company authorities due to low costs and uncomplicated formal requirements. The entry into force of Regulation 2017/1129 resulting in the amendment of the Public Offering Act has changed the definition of a public offering in Polish law, significantly expanding its scope. At the same time, transactions that were previously considered private placements have become public offerings under the new legal definition. In this article the author compares the solutions of the American federal law regarding private and public offerings to the Polish regulations. Moreover, he proves that American law has developed a clear distinction between public and private offerings, treating private offerings as a separate class of offerings, while Polish law treats private placements as a type of public offerings. The author also tries to create a definition of a private placement that is consistent with the new legal environment in Poland.

Oferta prywatna jako oferowanie papierów wartościowych lub akcji określonej grupie inwestorów jest chętnie wybierana przez władze spółek ze względu na niskie koszty i nieskomplikowane wymogi formalne. Wejście w życie rozporządzenia 2017/1129 skutkujące nowelizacją ustawy o ofercie publicznej spowodowało zmianę definicję oferty publicznej w polskim prawie, znacznie rozszerzając jej zakres. Jednocześnie transakcje, które były uznawane do tej pory za oferty prywatne, stały się zgodnie z nową definicją legalną ofertami publicznymi. W niniejszym artykule autor porównuje rozwiązania amerykańskiego prawa federalnego dotyczące ofert prywatnych i publicznych do polskich regulacji. Ponadto stawia tezę, że prawo amerykańskie wykształciło wyraźne rozróżnienie pomiędzy ofertą publiczną a prywatną, traktując ofertę prywatną jako osobną klasę ofert, podczas gdy prawo polskie traktuje ofertę prywatną jako jeden z rodzajów oferty publicznej. Autor stara się także stworzyć definicję oferty prywatnej zgodną z nowym otoczeniem prawnym w Polsce.
Pojęcie oferty prywatnej w prawie polskim i amerykańskim prawie federalnym: Analiza porównawcza
Keywords: public offering; private placement; the Polish Financial Supervision Authority; comparative law; oferta publiczna; oferta prywatna; Komisja Nadzoru Finansowego; prawo porównawcze